Gestational Exposure to Perchlorate in the Rat: Thyroid Hormones in Fetal Thyroid Gland, Serum, and Brain. (6th April 2022) - Gilbert, Mary E; Hassan, Iman; Wood, Carmen; O'Shaughnessy, Katherine L; Spring, Stephanie; Thomas, Susan; Ford, Jermaine
Abstract: Iodine is essential for the production of thyroid hormones. Perchlorate is an environmental contaminant that interferes with iodine uptake into the thyroid gland to reduce thyroid hormone synthesis. As thyroid hormones are critical for brain development, exposure to perchlorate during pregnancy is of concern for the developing fetal brain. In this study, we (1) define profiles of thyroid hormone in the maternal and fetal compartments of pregnant rats in response to inhibition of the sodium-iodide symporter (NIS) by perchlorate and (2) expand inquiry previously limited to serum to include fetal thyroid gland and brain. Perchlorate was added to the drinking water (0, 1, 30, 300, and 1000 ppm) of pregnant rat dams from gestational days (GD) 6–20. On GD20, blood, thyroid gland, and brain were collected from the fetus and dam for thyroid hormone and molecular analyses. Thyroid gland and serum thyroid hormones were dose-dependently reduced, with steeper declines evident in the fetus than in the dam. The thyroid gland revealed perturbations of thyroid hormone-action with greater sensitivity in the fetus than the dam. Thyroid hormones and thyroid hormone-responsive gene expression were reduced in the fetal cortex portending effects on brain development. These findings are the first quantitative assessments of perchlorate-induced deficits in the fetal thyroid gland and fetal brain. We provide a conceptual framework to develop a quantitative NIS adverse outcome pathway for serum thyroid hormone deficits and the potential to impact the fetal brain. Such a framework may also serve to facilitate the translation of in vitro bioactivity to the downstream in vivo consequences of NIS inhibition in the developing fetus.